Alfabetização e ensino à luz da consciência fonológica: um processo a partir da variação linguística - Lima, Fabiana Silva de Lira (2023)
Literacy is a process that promotes the development of skills related to reading and writing, since it involves several teaching practices for the systematization of knowledge of the Alphabetic Writing System (SEA) and the manipulation of phonemes and graphemes that are directly linked to the act of reading and writing. The construction of knowledge of the relationships between phonemes and graphemes, present in the literacy cycle, can be considered somewhat complex, since the understanding of the regular and irregular relationships between letters and sounds does not happen instantly, and is something that requires teaching with planned and articulated practices, as a way of making students able to develop the coding and decoding skills necessary for the acquisition of fluid reading and assertive writing, as well as practices aimed at the development of literacy, allowing the student to participate in various communicative contexts. Given this reality, the need arose to investigate and propose teaching practices that contribute to the development of phonological awareness, based on studies that consider variation in spoken language and its relationship with written language in the literacy process. To this end, we set the following general objective: to analyze how activities that discuss variation and phonological phenomena can contribute to the process of teaching literacy. To provide guidance for each stage, we set the following specific objectives: 1. To investigate studies focused on phonological awareness and variation and teaching and their contributions to the literacy process with literacy; 2. To promote reflection on the importance of knowing and respecting linguistic diversity; 3. To propose activities focused on the acquisition of reading and writing in order to develop phonological awareness, based on language variation; 4. To prepare a pedagogical notebook with a proposal that contributes to the literacy and literacy process, developing phonological awareness based on linguistic variation. This study had as participants students from the 2nd year of Elementary School and was developed through a qualitative approach, whose fieldwork took place in an interventionist way, through action research, using the bibliographic review and the realization of pedagogical workshops as data generating procedures. To constitute the corpus of the work, the activities proposed as pedagogical mediation carried out during the workshops were analyzed. This is how the research is structured, based on the study of the literature of some authors who deal with the theme addressed: Kleiman (2005), Tfouni (2006), Bortoni-Ricardo (2006), Lemle (2009), Vieira (2014), Moraes (2020), Soares (2020; 2021), among others. Data analysis was performed using Triangulation of Methods, which proposes an analysis through the articulation between dialogue with authors, empirical data and an analysis of the situation, enabling an understanding of the context. The systematization of the proposed skills occurred through the sequential execution of activities that developed the understanding between the variation of the spoken language and its relationship with the written language, resulting in a pedagogical notebook containing the step-by-step of this proposal, in order to contribute to the development of reading and writing in the literacy process, as a way of leading students to become conscious users of the language in its entirety. We can affirm that our objective was positively achieved, since, inserted in different contexts, we reflected with the students on phonological aspects of words, through their speech, identifying traces of variation that need to be respected, since they are part of the historical, social and cultural constructions of each one, making it possible to reflect on the use of language in different contexts.